Development of a reliability model to analyse the causes of a poultry module failure - Shcherbovskykh, Serhiy; Spodyniuk, Nadiia; Stefanovych, Tetyana; Zhelykh, Vasyl; Shepitchak, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2016)
A mathematical model of reliability has been developed for a poultry module. The suggested reliability model is designed for quantitative analysis of the causes of such a system failure. The reliability of the module for keeping poultry is formalized with a fault tree, which sets logical conditions for the appearance of the system failure. A failure is recognized as formation of such a microclimate in the area of keeping poultry that potentially threatens the birds’ lives and health. For the module, we distinguish between two main types of violation in its functioning – violation of the temperature control and violation of the ventilation mode in the box. The first case can pose the poultry a threat of hypothermia, and the second results in a lack of fresh air. The fault tree is used to form a homogeneous Markov model that is applied to calculate the characteristics of the system reliability. The model has helped determine the probabilistic characteristics of all causes of failure and the percentage contribution of each cause for a specified operating time. It has been revealed that the biggest contribution to the module failure is made by a simultaneous incapacity of the infrared heater and the calorifier, the exhaust fan failure, and the supply fan incapacity.